Financing politics in democratic countries : A comparative analysis of funding for political parties and election campaigns in France, Germany, and the United Kingdom. - Karpovich, Maksim; Vymětal, Petr; Dítětová, Adéla; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Political parties are often considered to be the key element in the effective working of a representative government and having a transparent and equitable party and campaign finance regulatory framework is crucial for the rule of law and democracy. This paper aims to answer the questions of what constitutes an effective political finance regulatory framework and which regulatory practices strengthen the democratic governance, and which carry potential risks. For this purpose, the examples of three countries with an established and rather longstanding tradition of democracy – France, Germany, and the United Kingdom – are analyzed here. This paper concludes that there is no one-size-fits-all approach when it comes to the laws regulating political finance, and it is a rather impossible task to pick a winner among the three countries. Yet, all thee strive to increase transparency and reduce the role of interested money in politics, and valuable lessons in this area can be learned from their experiences.
Vedoucí práce: Petr Vymětal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses